2003
DOI: 10.1002/dmrr.401
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction velocity and evoked potential latencies in streptozotocin‐diabetic rats: effects of treatment with an angiotensin converting enzyme inhibitor

Abstract: Enalapril partially prevents the development of neurophysiological alterations in the peripheral and central nervous system and partially reverses deficits in brain stem auditory evoked potential latencies in STZ-diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Malik, et al (1998) demonstrated that the angiotensin converting enzyme inhibitor trandolapril improved peripheral neuropathy in normotensive patients with diabetes. In studies with diabetic rats we and others have shown that inhibition of angiotensin converting enzyme can improve diabetic peripheral neuropathy (Aggarwal et al, 2001; Cameron et al, 1993; Coppey et al, 2006; Manschot et al, 2003). α-Lipoic acid, also known as thioctic acid, is an organosulfur compound derived from octanoic acid.…”
Section: Discussionmentioning
confidence: 92%
“…Malik, et al (1998) demonstrated that the angiotensin converting enzyme inhibitor trandolapril improved peripheral neuropathy in normotensive patients with diabetes. In studies with diabetic rats we and others have shown that inhibition of angiotensin converting enzyme can improve diabetic peripheral neuropathy (Aggarwal et al, 2001; Cameron et al, 1993; Coppey et al, 2006; Manschot et al, 2003). α-Lipoic acid, also known as thioctic acid, is an organosulfur compound derived from octanoic acid.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, angiotensin-converting enzyme inhibitors have shown an improvement of nerve conduction velocity in distal symmetrical polyneuropathy. 92) Thus, the pathophysiological process of autonomic neuropathy is closely related with vascular function in subjects with diabetes.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…neurological and cognitive complications, and dysfunctions of the visual system (Manschot et al 2003, Gregori et al 2006. Therefore, we planned to evaluate the following parameters: 1) Brain cortex flash-visual evoked potentials (VEPs) and rapid oscillatory potentials (OPs), because in stable type 2 diabetes and in diabetes models both color-VEP and VEP latency are consistently slower vs controls.…”
Section: Diabetes-related Stress Mechanismsmentioning
confidence: 99%